Recovery rate and predictors among children aged 6–59 months with severe acute malnutrition in Addis Ababa, Ethiopia: a retrospective follow-up study - Getahun, Genanew Kassie; Andabo, Wondimu Ayele; Shewamare, Abraham; Birhanu, Molla Yigzaw (Frontiers in Pediatrics, 2024)
Introduction: Severe acute malnutrition (SAM) is a critical public health concern in Ethiopia, contributing to high morbidity and mortality rates among children. Despite the improvement in hospital coverage and the development of standardized WHO treatment guidelines, recent reviews indicated a wide range in recovery rates (34-88%) due to several context-specific factors. Understanding the factors influencing the recovery time can help inform targeted interventions and improve the overall management of SAM cases. Therefore, the aim of this study was to assess the time to recovery and predictors of children aged 6-59 months with severe acute malnutrition in Addis Ababa, Ethiopia, in 2023.Methods: An institutional-based retrospective follow-up study was conducted among children aged 6-59 months admitted to Tirunesh Beijing Hospital, Addis Ababa, Ethiopia, from July 2019 to June 2023. The Kaplan-Meir estimate and survival curve were used to compare the time to recovery using a log-rank test among different characteristics. A Cox proportional hazard regression analysis model was used to identify significant predictors of time to recovery. Finally, a p-value less than 0.05 were used to declare a significant association.The median survival time to recovery was 17 (95% CI: 16.39, 17.60) days, and the incidence rate of recovery from SAM was 37.8 per 1000 child days. Moreover, exclusive breast feeding (Adjusted Hazard Ratio (aHR): 1.97, 95% CI: 1.45, 2.68), amoxicillin provision (aHR:1.62, 95% CI: 1.11, 2.35), and deworming (aHR: 2.14, 95% CI: 1.48, 3.09) were protective factors. However, complications at admission (aHR: 0.41, 95% CI: 0.23, 0.73) and diarrhea during admission (AHR: 0.64, 95% CI: 0.45, 0.91), were identified as a risk factors of recovery from SAM.The time to recovery among the current study participants was low compared with the sphere standard. Besides, exclusive breast feeding, complications at admission, diarrhea, amoxicillin provision, and deworming were independent predictors. Therefore, appropriate provision of routine medication and early management of medical comorbidity as per the national SAM management protocol can reduce the mortality of child with severe acute malnutrition significantly.